CARDIOPULMONARY EXERCISE TEST AND ECHOCARDIOGAPHIC FINDINGS IN HOSPITALISED POST SARS-COV-2 PATIENTS: THE EFFECT OF ARTERIAL HYPERTENSION. (June 2022) - Kariori, Maria; Fragoulis, Christos; Chrysochoou, Christina; Leontsinis, Ioannis; Mantzouranis, Emmanoyil; Iliakis, Panagiotis; Konstantinidis, Dimitrios; Konstantinou, Konstantinos; Andrikou, Ioannis; Kalos, Theodoros; Grigoriou, Kalliopi; Tsioufis, Konstantinos
Abstract : Objective: There is little data concerning the impact of arterial hypertension (HTN) on the cardiopulmonary status and right ventricle (RV) function of patients with SARS-Cov-2 infection. The purpose of our study was to investigate whether HTN affects the functional status of hospitalized for SARS-Cov-2 patients, using cardiopulmonary test and echocardiographic parameters, 3 months after the first day of infection. Design and method: Subjects who were hospitalized and survived Covid-19 infection were divided into two groups according to history of HTN. All subjects underwent cardiorespiratory exercise using Bruce or modified Bruce protocol evaluating all parameters. Echocardiographic findings including right ventricle strain were analyzed using an offline program. Results: A total population of 52 hospitalized Sars-Cov-2 patients with a mean age of 57 ± 11.5 years were evaluated 3 months after the symptoms onset. Males amounted to 51.9 %. History of coronary artery disease was recorded in 15.4% of them. In hypertensive subjects, age (63 ± 8 vs. 52 ± 11 years, p < 0.001), BMI (29.9 ± 4.6 vs. 27.1 ± 5.8 kg/m2, p:0.03) and BSA (2.1 ± 0.25 vs. 2 ± 0.9 m2, p:0.04) were significantly higher. When analyzing cardiopulmonary test parameters, only maximum systolic blood pressure ((SBP, mmHg), 190 ± 21 vs.171 ± 26, p: 0.02) at peak and during the 1st minute of recovery (180 ± 23 vs. 157 ± 27 mmHg, p: 0.005) were higher comparing to normotensive subjects. Furthermore, diameter of left atrium ((LA, mm), 42 ± 6 vs.38 ± 6 p: 0.009), left ventricle ejection fraction ((LVEF, %), 48 ± 11 vs. 57 ± 6, p:0.004) and the absolute mean value of right ventricle strain ((RVLS, %), 9.1 ± 4 vs. 12.7 ± 5.4, p:0.04) differed significantly between two groups. Using linear regression analysis adjusted for age, gender, HTN, coronary heart disease and LVEF, HTN Conclusions: Our study highlighted negative impact of HTN both in right and left ventricle functionality, implying HTN as a negative independent predictive factor for right ventricle strain in patients hospitalized for SARS-Cov-2.